Drug and alcohol use and treatment for Australian Indigenous and non-Indigenous prisoners: demand reduction strategies. Issue 1 (16th March 2015) - Dolan, Kate; Rodas, Ana; Bode, Adam
Abstract : Purpose: – The purpose of this paper is to compare the use of drugs and alcohol by Indigenous and non-Indigenous prisoners and examine relevant treatment in Australian prisons. Design/methodology/approach: – Prison authorities were surveyed about alcohol and drug use by prisoners prior to and during imprisonment and drug and alcohol treatment programs in prison. The literature was review for information on alcohol and drug use and treatment in Australian prisons. Findings: – In 2009, over 80 percent of Indigenous and non-Indigenous inmates smoked. Prior to imprisonment, many Indigenous and non-Indigenous inmates drank alcohol at risky levels (65 vs 47 percent) and used illicit drugs (over 70 percent for both groups). Reports of using heroin (15 vs 21 percent), ATS (21 vs 33 percent), cannabis (59 vs 50 percent) and injecting (61 vs 53 percent) were similarly high for both groups. Prison-based programs included detoxification, Opioid Substitution Treatment, counselling and drug free units, but access was limited especially among Indigenous prisoners. Research limitations/implications: – Drug and alcohol use was a significant issue in Australian prisons. Prisoners were over five times more likely than the general population to have a substance use disorder. Imprisonment provides an important opportunity for rehabilitation for offenders. This opportunity is especially relevant to Indigenous prisoners who were more likely to use health services when in prison than in the community and given their vast over representations in prison populations. Practical implications: – Given the effectiveness of treatment in reducing re-offending rates, it is important to expand drug treatment and especially culturally appropriate treatment programs for Indigenous inmates. Originality/value: – Very little is known about Indigenous specific drug and alcohol programs in Australian prisons.